Fylogeneze znaků srsti kočkovitých šelem (Felidae). - Pavliska, Petr (Jihočeská univerzita, 2010)
Phylogeny of several fur characters has been studied in the family Felidae. Fur characters were compared with other morphological, ecological and behavioral characters based on basic phylogenetic parameters (L, CI, RI). I detected character states for ancestor of specific well-supported clades (lineages) and described characters evolution in Felidae. Some basic fur characters were statistically analyzed for possible correlations with some ecological and behavioral characters.
Phylogeny of fur characters in Felidae.
Keywords: Felidae; phylogeny; fur; Felidae; phylogeny; fur